CD26 as a potential therapeutic target for lung adenocarcinoma - Jungraithmayr, Wolfgang; Ohm, Birte; Haberecker, Martina; Curioni-Fontecedro, Alessandra; Janker, Florian; Gil-Bazo, Ignacio; Soltermann, Alex; Kirschner, Michaela; Weder, Walter; Opitz, Isabelle; Jang, Jae-Hwi (Frontiers in Oncology, 2025)
IntroductionCD26/dipeptidyl peptidase 4 (CD26, DPP4) is a transmembrane exopeptidase that modulates tumorigenesis in different malignancies. We demonstrated before that CD26 inhibition decreases lung tumor growth in experimental models. Here, we analyzed the prognostic significance of CD26 expression and its correlation with epithelial-to-mesenchymal transition (EMT) markers in a large series of patients with non-small cell lung cancer (NSCLC).Patients and methodsNSCLC samples from operated patients were analyzed using immunohistochemistry (IHC) for the expression of CD26 and EMT markers. CD26 was scored semi-quantitatively employing tissue microarrays. Lung cancer cell lines [H460, Lewis lung carcinoma (LLC)] were tested for EMT markers, and a colony formation assay was used to test the effect of treatment with the CD26 inhibitor vildagliptin.ResultsTumor samples from 904 patients with NSCLC were analyzed. CD26 IHC expression was significantly higher in adenocarcinoma compared to squamous cell carcinoma (p < 0.0001). Patients with adenocarcinoma and CD26 expression had a better overall survival than patients without CD26 expression. The lack of CD26 expression was shown to be an independent risk factor for worse survival. CD26-expressing adenocarcinomas showed a higher expression of Vimentin and Elastin (p = 0.0027 and p < 0.0001, respectively), while E-cadherin expression was lower in this group of patients (p = 0.0021). In vitro, treatment with vildagliptin reduced the expression of Vimentin and the capacity for colony formation in H460 and LLC cell lines.Summary and conclusionThe correlation of CD26 expression in lung adenocarcinomas and better patient survival, the antiproliferative effect on tumor cells by CD26 inhibition, and an altered EMT status give rise to the hypothesis that CD26 inhibitors impact the biology and clinical course of lung adenocarcinomas.